Integrative Proteomic and Phosphoproteomic Profiling Reveals Molecular Mechanisms of Hypoxic Adaptation in Brandt’s Voles (Lasiopodomys brandtii) Brain Tissue - Panqin Wang; Yongyan Liu; Yimeng Du; Yiwen Gao; Tian Shao; Weifeng Guo; Zhenlong Wang; Han Cheng (Cells)
Rapid ascent to high altitudes by unacclimatized individuals significantly increases the risk of brain damage, given the brain’s heightened sensitivity to hypoxic conditions. Investigating hypoxia-tolerant animals can provide insights into adaptive mechanisms and guide prevention and treatment of hypoxic-ischemic brain injury. In this study, we exposed Brandt’s voles to simulated altitudes (100 m, 3000 m, 5000 m, and 7000 m) for 24 h and performed quantitative proteomic and phosphoproteomic analyses of brain tissue. A total of 3990 proteins and 9125 phosphorylation sites (phospho-sites) were quantified. Differentially expressed (DE) analysis revealed that while protein abundance changes were relatively modest, phosphorylation levels exhibited substantial alterations, suggesting that Brandt’s voles rapidly regulate protein structure and function through phosphorylation to maintain cellular homeostasis under acute hypoxia. Clustering analysis showed that most co-expressed proteins exhibited non-monotonic responses with increasing altitude, which were enriched in pathways related to cytokine secretion regulation and glutathione metabolism, contributing to reduced inflammation and oxidative stress. In contrast, most co-expressed phospho-sites showed monotonic changes, with phospho-proteins enriched in glycolysis and vascular smooth muscle contraction regulation. Kinase activity prediction identified nine hypoxia-responsive kinases, four of which belonging to the CAMK family. Immunoblot validated that the changes in CAMK2A activity were consistent with predictions, suggesting that CAMK may play a crucial role in hypoxic response. In conclusion, this work discovered that Brandt’s voles may cope with hypoxia through three key strategies: (1) vascular regulation to enhance cerebral blood flow, (2) glycolytic activation to increase energy production, and (3) activation of neuroprotective mechanisms.